Mora'nın istirdadına dair bir kaynak değerlendirmesi ve Nâdir'in Vâkı'ât-ı Gazavât'ı - (:unkn) unknown (My University, 2009)
Osmanlı, idaresine tam olarak II. Bayezid zamanında giren Mora Yarımadası’nı 1699 Karlofça antlaşmasıyla terk etmek zorunda kalmış, 1715 yılında ise yeniden kontrolüne almıştı. Mora’nın bu yeniden fethini konu alan bazı eserler günümüze ulaşmıştır. Bu makalenin ilk kısmında; 18. yüzyılın başlarında Mora’nın Osmanlılar tarafından yeniden fethi ile ilgili ulaşılabilen kronikler arasında bir değerlendirme yapılmıştır. İkinci kısmında ise; 1715 Mora’nın istirdâdını, 1716’daki Avusturya ile Varadin’de yapılan mücadeleyi ve Mora etrafında gelişen 1717 muharebelerini anlatan Nâdir’in Vâkı‘ât-ı Gazavât adlı eseri takdim edilmiştir.

Fully incorporated to the Ottoman administration at the reign of Bayezid II, the Ottomans ceded the Morea in the Treaty of Karlowitz in 1699. However, it regained the control in 1715. Some works on the re-conquest of Morea have survived to the present. The first part of this paper makes a comparison on the available chronicles about the re-conquest of the Morea by the Ottomans. The second part deals with the re-conquest of the Morea in 1715, the War of Varadin between the Ottomans and the Austrians in 1716 and it also introduces the work of Nâdir titled Vâkı‘ât-ı Gazavât which narrates the battles fought around the Morea in 1717.
An evaluation of source about reconquest morea and Nâdir's Vâkı'ât-ı Gazavât
Keywords: Arkeoloji; Kültürel Çalışmalar; Tarih